Men, ideas & politics - Drucker, Peter F. (Harper & Row, 1971)
This term is not to be found in any university catalogue. But the only thing that is new about political ecology is the name. As asubject matter and human concern, it can boast ancient lineage, going back all the way to herodotus and Thucydides.